Intelligent Analysis of Employee Data for Decision Support in Enterprises: A Survey of User Needs (Journal of Universal Excellence, 2026)
Research Question (RQ): Our research focuses on the study of companies' interest in automatic employee absence forecasting services and asks the following question: how to make an effective analytical tool for predicting employee absence from the workplace?Purpose: The purpose of the research is to determine whether there is an interest in automatic absence forecasting services among different companies, and to analyze their needs with the aim of the correct design of software (analytical tool) that would offer such services.Method: A survey questionnaire was used, which is intended for companies that use the MojeUre system for recording working hours (https://mojeure.si/) in order to obtain data on functionalities that could improve the prediction of employee absences and help in the organization of work.Results: The survey gathered information from users of the MojeUre system about suitable absence forecasts for companies. This information is important in the development of an analytical tool. We also conclude that predicting absence from the workplace is useful for organizing employees in case of unexpected absence.Organization: The developed analytical tool would enable companies to reorganize employees more easily and more meaningfully in case of anticipated absence, which would consequently have an impact on less loss of work performed by employees.Society: A tool for predicting employee absence has positive effects on society: better planning, greater efficiency, lower costs, easier reorganization of work.Originality: There is no similar analytical tool on the market that would predict employee absence based on historical data. Otherwise, there are tools for decision support, but not for analyzing employee absences.Limitations / further research: The survey conducted was limited to users of the existing MojeUre system, which means that we do not have feedback from other companies that want to use the tool to predict employee absences.
Keywords: survey; intelligent analysis; data mining; decision support; working time record